2001
DOI: 10.1542/peds.107.2.344
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Body Composition in Relation to Body Mass Index

Abstract: Unlike adults, annual increases in BMI during childhood are generally attributed to the lean rather than to the fat component of BMI. Because the properties of BMI vary during childhood, health care professionals must consider factors such as age and sex when interpreting BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
314
1
18

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 403 publications
(350 citation statements)
references
References 24 publications
13
314
1
18
Order By: Relevance
“…The lean body mass rather than the fat mass contributes the annual increment in the BMI of school-aged children and adolescents [27]. However, the BMI of children and adolescents is strongly associated with blood pressure [28], as well as adiposity (measured by dual-energy X-ray absorptiometry) and metabolic risk factors, including glucose, insulin, and lipids [29].…”
Section: Discussionmentioning
confidence: 99%
“…The lean body mass rather than the fat mass contributes the annual increment in the BMI of school-aged children and adolescents [27]. However, the BMI of children and adolescents is strongly associated with blood pressure [28], as well as adiposity (measured by dual-energy X-ray absorptiometry) and metabolic risk factors, including glucose, insulin, and lipids [29].…”
Section: Discussionmentioning
confidence: 99%
“…Using hydrodensitometry in a study of children (aged 8-18 years), Maynard et al (2001) revealed that weight increase in boys was mostly related to the increase in muscle mass, while variations in fat mass were slightly negative between the ages Fat mass in healthy population S Aguado Henche et al of 14 and 15, and between the ages of 16 and 17. In girls, weight increases related mostly to the increase in lean mass through the age of 16, and thereafter to increases in fat mass.…”
Section: Discussionmentioning
confidence: 99%
“…A major limitation of BMI is that it does not differentiate between weight that is fat and weight that is muscle, and therefore may lead to the misclassification of very muscular individuals as overweight. Whether fat or lean mass is dominant depends on age, sex, pubertal stage and ethnicity (Daniels et al, 1997;Maynard et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a deficit of the body mass may be due to a fat-free mass deficit or mobilization of fat mass, or both combined (Heber et al, 1996). In terms of body composition, it has been observed that, in each sex, annual increases in BMI were driven primarily by increases in fat free mass/ stature 2 until late adolescence, with increases in total body fat/stature 2 contributing to a larger proportion of the BMI increases in girls than in boys (Maynard et al, 2001). In a group of 280 adolescents from Zaragoza, we measured BF% by DXA (Rodríguez et al, 2004); obesity status was defined by IOTF cutoff values (Cole et al, 2000), and subjects were therefore classified into three groups: normal-weight, overweight and obese.…”
Section: Discussionmentioning
confidence: 99%